2020 IEEE International Joint Conference on Biometrics (IJCB) 2020
DOI: 10.1109/ijcb48548.2020.9304893
|View full text |Cite
|
Sign up to set email alerts
|

Generating Master Faces for Use in Performing Wolf Attacks on Face Recognition Systems

Abstract: Face authentication is now widely used, especially on mobile devices, rather than authentication using a personal identification number or an unlock pattern, due to its convenience. It has thus become a tempting target for attackers using a presentation attack. Traditional presentation attacks use facial images or videos of the victim. Previous work has proven the existence of master faces, i.e., faces that match multiple enrolled templates in face recognition systems, and their existence extends the ability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 43 publications
(101 reference statements)
0
33
0
Order By: Relevance
“…This allows better control of the image synthesis process and results in the generation of quality and more detailed images. c) Master sample attacks: A parallel work that we became aware of post-publication [27] attempts to generates faces that are similar to a large portion of the faces in a given dataset using StyleGAN but with a different evolutionary strategy, which is one of our baselines (CMA-ES). In the field of finger print verification, Roy et al [33] have suggested to exploiting the lower quality of partial fingerprint systems to generate fingerprint templates that can be matched to a large number of users' fingerprints, without any knowledge of the actual user.…”
Section: Related Workmentioning
confidence: 99%
“…This allows better control of the image synthesis process and results in the generation of quality and more detailed images. c) Master sample attacks: A parallel work that we became aware of post-publication [27] attempts to generates faces that are similar to a large portion of the faces in a given dataset using StyleGAN but with a different evolutionary strategy, which is one of our baselines (CMA-ES). In the field of finger print verification, Roy et al [33] have suggested to exploiting the lower quality of partial fingerprint systems to generate fingerprint templates that can be matched to a large number of users' fingerprints, without any knowledge of the actual user.…”
Section: Related Workmentioning
confidence: 99%
“…They worked with small sensors of smartphones which acquire a lot of partial minutiae-based feature vectors. It was later improved with machine learning based approaches in [31,30,4] and recently applied on face recognition in [23].…”
Section: Definitions and Related Workmentioning
confidence: 99%
“…In 3D, this drops to 7.5% indicating that for higher-dimensional representations the effectiveness might further decrease. ate any user without having access to information about the enrolled subject [17]. Since face recognition systems (FRS) are spreading worldwide and are increasingly involved in our daily life activities [26], successful MasterFace attacks pose a great threat to these systems.…”
Section: Introductionmentioning
confidence: 99%
“…In that work, the authors report that a single face can cover more than 20% of the identities in the used database (for a given FR model at a threshold for a false match rate of 10 −3 ). Also, Nguyen et al [17,16] proposed a similar method for generating MasterFaces and demonstrated that these attacks can successfully compromise FRS. However, these works (a) make use of older FRS, (b) consist of only limited cross-dataset and cross-model evaluations, and (c) conduct their experiments on testing data of small size and variance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation